MONITORING THE ACCURACY OF OBSERVATIONS OF PASSIVE OBJECTS ON THE BASIS OF THE INTERNATIONAL LASER RANGING SERVICE (ILRS) DATA - Kara, I. V. (Одеські астрономічні публікації, 2009)
Today, the problem of pollution of the near-Earth space environment is becoming more acute. In view of that, a larger number of stations for observation and tracking of artificial earth satellites (AES) and space debris objects have been set up. The accuracy of the ephemerides of such objects depends on the quality of the observations obtained. Therefore, the possibility of efficient quality control and monitoring the accuracy of the gathered observations is extremely essential. The suggested method allows of promptly conducting a check on the correctness of the data obtained. The coordinate data of the International Laser Ranging Service (ILRS) are assumed as a basis of the method mentioned above. The developed mathematical software (MS) enables observers to analyze their observations efficiently and without assistance in order to reveal and solve arisen instrumental problems opportunely.